Sulforaphane Potentiates Anticancer Effects of Doxorubicin and Cisplatin and Mitigates Their Toxic Effects - Calcabrini, Cinzia; Maffei, Francesca; Turrini, Eleonora; Fimognari, Carmela (Frontiers in Pharmacology, 2020)
The success of cancer therapy is often compromised by the narrow therapeutic index of many anticancer drugs and the occurrence of drug resistance. The association of anticancer therapies with natural compounds is an emerging strategy to improve the pharmaco-toxicological profile of cancer chemotherapy. Sulforaphane, a phytochemical found in cruciferous vegetables, targets multiple pathways involved in cancer development, as recorded in different cancers such as breast, brain, blood, colon, lung, prostate, and so forth. As examples to make the potentialities of the association chemotherapy raise, here we highlight and critically analyze the information available for two associations, each composed by a paradigmatic anticancer drug (cisplatin or doxorubicin) and sulforaphane.